2017
DOI: 10.1634/theoncologist.2017-0284
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Symptom Control of Diarrhea and Flushing in Patients with Neuroendocrine Tumors Treated with Lanreotide Depot/Autogel: Results from a Randomized, Placebo-Controlled, Double-Blind and 32-Week Open-Label Study

Abstract: This study prospectively collected daily patient-reported data on diarrhea and flushing from the ELECT trial to evaluate the direct impact of lanreotide depot on patients' relief of carcinoid syndrome symptoms. Treatment with lanreotide depot was associated with significant reductions in the percentages of days patients reported symptoms of diarrhea and flushing, as well as reductions in the frequency and severity of daily symptoms compared with placebo during 16 weeks of double-blind treatment. These improvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Previous post hoc analyses of the ELECT data have demonstrated that lanreotide patients were responsive with respect to their reported reduction in the symptoms of CS, and this was consistent across subgroups. In a post hoc analysis where patient-reported symptom data were combined to provide an average daily composite score, based on daily frequency and severity of symptoms, patients treated with lanreotide showed greater reductions in diarrhea or flushing compared with patients treated with placebo 19. Further subgroup analysis of ELECT found that the benefit of lanreotide compared to placebo, including greater CS symptom control, was consistent across treatment-naïve and octreotide-experienced patients, where lanreotide-treated subjects showed greater carcinoid symptom control in both samples 20.…”
Section: Discussionmentioning
confidence: 99%
“…Previous post hoc analyses of the ELECT data have demonstrated that lanreotide patients were responsive with respect to their reported reduction in the symptoms of CS, and this was consistent across subgroups. In a post hoc analysis where patient-reported symptom data were combined to provide an average daily composite score, based on daily frequency and severity of symptoms, patients treated with lanreotide showed greater reductions in diarrhea or flushing compared with patients treated with placebo 19. Further subgroup analysis of ELECT found that the benefit of lanreotide compared to placebo, including greater CS symptom control, was consistent across treatment-naïve and octreotide-experienced patients, where lanreotide-treated subjects showed greater carcinoid symptom control in both samples 20.…”
Section: Discussionmentioning
confidence: 99%
“…26 Clinical trials also support a reduction in the number of days patients on lanreotide experience diarrhea and/or flushing. 27 However, recent data from a large observational cohort shows that 43% of study subjects still experienced diarrhea after 6 months of lanreotide therapy compared to 44% at baseline. 28 The most common adverse effects associated with SSAs include nausea, abdominal cramps, loose stools, mild steatorrhea (due to meal-stimulated inhibition of pancreatic exocrine secretion and subclinical fat malabsorption), and flatulence.…”
Section: Historical Perspective Of Somatostatin Analogues and The Evolution Of The Lar-based Treatment Paradigmmentioning
confidence: 99%
“…According to current guidelines, treatment with either octreotide or lanreotide is recommended as the initial first-line treatment in patients with CS (Table 5) [1]. If treatment with the standard dose is not effective, high-dose SSA therapy can be administered [57][58][59]. Tryptophan Hydroxylase Inhibitors: Telotristat, an oral inhibitor of tryptophan hydroxylase, has been investigated in TELESTAR and TELECAST phase III studies (Table 5) [72].…”
Section: Diarrhea Associated With Carcinoid Syndrome or Other Hormonamentioning
confidence: 99%
“…According to current guidelines, treatment with either octreotide or lanreotide is recommended as the initial first-line treatment in patients with CS ( Table 5 ) [ 1 ]. If treatment with the standard dose is not effective, high-dose SSA therapy can be administered [ 57 , 58 , 59 ].…”
Section: Management Options and Treatment Strategiesmentioning
confidence: 99%